Kajian Faktor – Faktor Yang Mempengaruhi Keselamatan Kesehatan dan Lingkungan Kerja Proyek Konstruksi - Angelica, Gibretha; Nuswantoro, Waluyo (Jurnal Basement : Jurnal Teknik Sipil, 2026)
The increase in infrastructure development in Palangka Raya City has an impact on increasing complexity and risks in construction projects, so the implementation of Safety, Health, and the Work Environment is a crucial aspect. This study aims to identify and analyze the factors that affect the implementation of Occupational Safety and Health in the construction project environment in Palangka Raya City. The method used is a literature study with a qualitative descriptive approach through secondary data analysis sourced from scientific journals, books, and related regulations in the period from August to September 2025. The results of the study show that the success of the implementation of K3L is determined by 3 main factors, namely occupational safety, occupational health, and work environment, which consists of 15 supporting subfactors. Occupational safety factors include the use of Personal Protective Equipment (PPE), equipment inspection, and consistent supervision. Occupational health factors include the provision of hygiene facilities, the arrangement of rest times, and worker health checks. Meanwhile, work environmental factors include waste management, pollution control, and the application of environmentally friendly principles. This study provides a theoretical reference for the development of construction management science and provides practical guidance for contractors in improving work safety performance in a holistic, efficient, and quality manner.